Managing anxiety and uncertainty through social networking sites, how effectively can youth communicate online? - Bolong, Jusang; Sahharon, Hamizah; Omar, Siti Zobidah; Mohamed, Shazleen; Nordin Selat, Dewi Seribayu (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines the usage patterns of social networking sites among Malaysian youths and their Anxiety/Uncertainty Management levels. According to the anxiety and uncertainty management theory, members of a group should be cooperative, trustworthy, tolerant of diversity, and happy in order to affect their membership attitude and behavior. These days, youth choose to spend their time on social networking sites since they provide an effective virtual community platform for communication. Malaysian youths exhibit a nuanced understanding of personal and social identity, motivation to interact, reactions to others, social categorizations, situational processes, connection to others, ethical interactions, and overall communication effectiveness. This study surveyed 600 respondents, the findings highlight a deep-rooted integration of digital communication into the daily lives of Malaysian youths, with a significant majority having extensive experience of 11 to 20 years on SNS platforms. SNS platforms significantly reduced communication uncertainty, fostering positive relationships and smoother communication through active, passive, and interactive strategies. Locality plays a crucial role in anxiety and uncertainty management, with rural youths demonstrating better management compared to their urban counterparts, attributed to stronger social cohesion, tighter networks, and communal lifestyles. The study suggests that addressing anxiety and uncertainty can improve communication quality in virtual settings, particularly in rural areas. Social media can promote cultural integration and acceptance among diverse groups. A balanced approach to communication, emphasizing ethical interactions, can maximize its benefits. The findings can be used to design targeted interventions and promote positive digital engagement practices among Malaysian youths.